Work-Family Conflict Directions, Psychological Well-Being, and Performance in Public Sector Employees - Julias Penata Utama; Fanny Martdianty (Annals of Human Resource Management Research, 2026)
Purpose: This study examines the direct and indirect effects of work-to-family conflict and family-to-work conflict on job performance through psychological well-being among employees of Statistics Indonesia. Methodology: A quantitative explanatory design with a cross-sectional self-report survey was employed. Data were collected from 333 civil servant employees of Statistics Indonesia from January to February 2026 and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with LISREL 8.8. Results: Work-to-family conflict and family-to-work conflict had negative effects on psychological well-being, whereas psychological well-being had a positive effect on job performance. Family-to-work conflict negatively affects job performance. In contrast, work-to-family conflict had a positive direct effect on job performance, contrary to the hypothesized direction. Mediation analysis revealed that psychological well-being mediated both relationships. Competitive partial mediation was found in the work-to-family conflict–job performance relationship, whereas complementary partial mediation was found in the family-to-work conflict–job performance relationship. Conclusions: Psychological well-being is an important mechanism linking interrole conflict and job performance. The findings also confirm that work-to-family conflict and family-to-work conflict should be treated as distinct constructs. Limitations: This study is limited by its cross-sectional design, self-reported data, purposive sampling, and single organizational context. Contributions: This study extends the work-family conflict literature by applying the Conservation of Resources theory to a strategic public-sector institution. Public organizations should manage workload, psychological support, and family responsive work arrangements to sustain employee performance.